Relational perceptions in high school physical education: teacher- and peer-related predictors of female students’ motivation, behavioral engagement, and social anxiety - Gairns, Felicity; Whipp, Peter R.; Jackson, Ben (Frontiers in Psychology, 2015)
Although researchers have demonstrated the importance of interpersonal processes in school-based physical education (PE), there have been calls for further studies that account for multiple relational perspectives and provide a more holistic understanding of students’ relational perceptions. Guided by principles outlined within self-determination theory and the tripartite efficacy model, our aim was to explore the ways in which students’ perceptions about their teacher and classmates directly and/or indirectly predicted motivation, anxiety, and engagement in PE. A total of 374 female high-school students reported the extent to which their teachers and classmates independently (a) engaged in relatedness-supportive behaviors, (b) satisfied their need for relatedness, and (c) were confident in their ability in PE (i.e., relation-inferred self-efficacy). Students also rated their motivation and anxiety regarding PE, and teachers provided ratings of in-class behavioral engagement for each student. Analyses demonstrated support for the predictive properties of both teacher- and peer-focused perceptions. Students largely reported more positive motivational orientations when they held favorable perceptions regarding their teacher and peers, and autonomous motivation was in turn positively related to behavioral engagement ratings. These findings offer novel insight into the network of interpersonal appraisals that directly and indirectly underpins important in-class outcomes in PE.